Stemness and chemoresistance in epithelial ovarian carcinoma cells under shear stress - Ip, Carman K.M.; Li, Shan-Shan; Tang, Matthew Y.H.; Sy, Samuel K.H.; Ren, Yong; Shum, Ho Cheung; Wong, Alice S.T. (Nature Publishing Group, 2016)
One of greatest challenges to the successful treatment of cancer is drug resistance. An exciting approach is the eradication of cancer stem cells (CSCs). However, little is known about key signals regulating the formation and expansion of CSCs. Moreover, lack of a reliable predictive preclinical model has been a major obstacle to discover new cancer drugs and predict their clinical activity. Here, in ovarian cancer, a highly chemoresistant tumor that is rapidly fatal, we provide the first evidence demonstrating the causal involvement of mechanical stimulus in the CSC phenotype using a customizable microfluidic platform and three-dimensional spheroids, which most closely mimic tumor behavior. We found that ovarian cancer cells significantly acquired the expression of epithelial-to-mesenchymal transition and CSC markers and a remarkable chemoresistance to clinically relevant doses of frontline chemotherapeutic drugs cisplatin and paclitaxel when grown under fluid shear stress, which corroborates with the physiological attainable levels in the malignant ascites, but not under static condition. Furthermore, we uncovered a new link of microRNA-199a-3p, phosphatidylinositol 3-kinase/Akt, and multidrug transporter activation in shear stress-induced CSC enrichment. Our findings shed new light on the significance of hydrodynamics in cancer progression, emphasizing the need of a flow-informed framework in the development of therapeutics.